A Comparative Study of the Biological Properties of Eugenia uniflora L. Fruits and Leaves Related to the Prevention of Cardiovascular Diseases - Jéssica Gonçalves; Nance Hontman; Rosa Perestrelo; José S. Câmara (Life)
Cardiovascular diseases (CVDs) remain the leading cause of death globally, emphasizing the need for effective preventive strategies. Plant-based foods, rich in phytochemicals, offer a promising potential in CVD prevention. This study investigated the antioxidant, anti-inflammatory, and antihypertensive properties of two Eugenia uniflora L. varieties (orange and purple pitanga) and their leaves. Their antioxidant activity was assessed using 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical cation scavenging activity assays, while their antihypertensive activity was evaluated through angiotensin-converting enzyme (ACE) inhibition. Their anti-inflammatory potential was determined via protein denaturation inhibition. Both fruit varieties exhibited similar bioactivities, with the purple variety showing a slightly higher activity, except in the DPPH and ABTS assays. The leaves consistently demonstrated the lowest activities across all assays. Free polyphenols, dominated by gallic acid, were quantified using µ-QuEChERS followed by ultrahigh-performance liquid chromatography (UHPLC-PDA). The orange variety contained the highest concentration of gallic acid (13.1 mg/100 g DW). These findings highlight the potential of Eugenia uniflora L. extracts as natural antioxidant, anti-inflammatory, and antihypertensive agents, suggesting their value in food, pharmaceutical, and cosmetic applications for promoting human health and preventing CVDs.